PEMBELAJARAN STRUKTUR KALIMAT DENGAN METODE KOOPERATIF MODEL TUTOR SEBAYA DI SEKOLAH DASAR - Suwardi Suwardi; Mukti Widayati (Klitika: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of the research Learning sentence structure in State Primary School Bendungan 1 Subdistrict Kedawung Sragen to: (1) describe the planning of learning sentence structure with cooperative peer tutor model method in State Primary School Bendungan 1; (2) describe the implementation of learning sentence structure with the cooperative model of peer tutors in State Primary School Bendungan 1; (3) describe the obstacles in learning sentence structure with the cooperative model of peer tutors in State Primary School Bendungan 1; and (4) describe the solution constraints learning sentence structure with the cooperative model of peer tutors in State Primary School Bendungan 1. This research is a descriptive qualitative research. The subject of this research is the head of the school, the teachers and students of the State Primary School Bendungan 1. Data obtained using observation, interviews, and analysis of documents. The validity of the data is performed using the triangulation of the data. Data analysis was done using interactive analysis. The results showed that: (1) Learning sentence structure with the cooperative model of peer tutors in State Primary School Bendungan 1. beginning with open lessons, do apersepsi, held a question and answer, and deliver learning objectives. (2) Learning is done by dividing students into small groups. Each group gets a text sentence structure to be discussed. The teacher explains how to write a sentence structure by giving an example in front of the class. The teacher also gives the opportunity to the students to present their work in front of the class. Teachers close the lesson by giving her the motivation to students. (3) the obstacles that appear in learning sentence structure in State Primary School Bendungan 1: Ego students still high, students are still reluctant to observe the sruktur sentences, and Students still trouble memorizing sentence structure. (4) the teacher's Effort in overcoming barriers in learning sentence structure in State Primary School Bendungan 1, namely: the teacher awaken students to dare to perform in front of the class, give understanding and comprehension on the importance of collaboration in writing sentence structure, the teacher pointed to students, but not forcing it, and teachers lead students to pronounce a sentence properly.